The effect of NSC-631570 (Ukrain) alone and in combination with pathogen-associated molecules on cell cycle distribution and apoptosis induction of mouse melanoma cells with different biological properties - Skivka, L.M.; Trompak, O.O.; Kudryavets, Yu.I.; Bezdenezhnykh, N.A.; Susak, Ya.M. (Experimental Oncology, 2010)
Monotherapy and combined application of antitumor drug NSC-631570 (Ukrain) are s uccessfully used for treatment of malignant melanoma since 1996. Melanoma cells of different origin have distinct susceptibility to components of Ukrain. Aim: To carry out comparative investigation of the effect of Ukrain used alone and in combination with pathogen associated molecules (PAM) on mitotic cycle and apoptosis induction in mouse melanoma cell lines with different biological properties. Methods: Two cell lines with different biological properties (rate of cell division, level of hematogenous metastasis, sensitivity to tumor necrosis factor (TNF)-induced apoptosis) established from B16 mouse melanoma cell line, were used. Apoptosis induction and cell viability were analyzed using trypan blue exclusion test, morphological criteria, DNA gel electrophoresis and flow cytometry. Cell cycle distribution of tumor cells was determined by flow cytometry. Transporters associated with antigen processing (TAP) genes expression was analyzed using reverse transcriptase-polymerase chain reaction (RT-PCR) method. Results: The melanoma cells with different metastatic capabilities differed ma rkedly by the growth rate, sensitivity to apoptosis inducers, and the character of TAP gene expression. Treatment of melanoma cells with Ukrain resulted in apoptosis induction in a dose dependent manner. Melanoma cells with high-metastatic properties were more sensitive to Ukrain than their low metastatic variants. However combined use of drug with PAM induced apoptosis more effectively in melanoma cells with low-metasta tic potential. Conclusion: Sensitivity to Ukrain in vitro may depend on biological properties of melanoma cells and may be modified by combined treatment of cells with TLR ligands. The results can be useful to optimize the regimen of mono and combined treatment of melanoma with Ukrain.